THE FEELINGS OF THE VISITORS PARTICIPATING IN RELIGIOUS TOURISM THE CASE OF VIRGIN MARY HOUSE IN IZMIR - Kömürcü, Simge; Sarıbaş, Özgür (International Journal of Contemporary Economics and Administrative Sciences, 2016)
Tourism is an important activity for the global economy around the world. This situation leads to an endless change and innovation. The answers to the changing needs and expectations of customers are contributes to this development. Many different researches are being developed to compete under these conditions. According to this study, identifying the feeling of the visitors participating in religious tourism is being able to request and an important response to meet the expectations. In this context, these research investigated feeling of the people who visit the Virgin Mary House. To quantify this phenomenon, semi-structured interview was used in this study which covered qualitative data collection techniques. As a result of this research, feelings of visitors in the holy place have been identified and their opinions and expectations have been evaluated.